Answer:
f(-6) = -2
Step-by-step explanation:
plug in k value (-6)
f(-6) = -6/2 + 1
theres two ways to solve for this
one way:
convert the whole number 1 to an improper fraction
f(-6) = -6/2 + 2/2
combine like terms
f(-6) = -4/2
divide -4 by 2
f(-6) = -2
second way:
divide -6 by 2
f(-6) = -3 + 1
combine like terms
f(-6) = -2
either way you get the same answer
use whichever is easiest for you
7.
(2b^2+7b^2+b)+(2b^2-4b-12)
(9b^2+b)+(2b^2-4b-12)
9b^2+b+2b^2-4b-12
11b^2+b-4b-12
11b^2-3b-12
8.
(7g^3+4g-1)+(2g^2-6g+2)
7g^3+4g-1+2g^2-6g+2
7g^3-2g-1+2g^2+2
7g^3-2g+1+2g^2
7g^3+2g^2-2g+1
Hope this helps!
<span>Watching television and reading newspaper are not independent events because P(A|B)=P(A) and P(B|A)=P(B) .
I might be wrong so try to look at it a little closer before you take my word for it.
</span>
Answer:
<h2><u><em>
342 m</em></u></h2>
Step-by-step explanation:
Calculate 50% of 684 m.
Give your answer in metres (m).
50% = 1/2
so
684 : 2 = 342 m